2005
DOI: 10.1176/appi.ajp.162.5.890
|View full text |Cite
|
Sign up to set email alerts
|

Countertransference Phenomena and Personality Pathology in Clinical Practice: An Empirical Investigation

Abstract: Countertransference phenomena can be measured in clinically sophisticated and psychometrically sound ways that tap the complexity of clinicians' reactions toward their patients. Countertransference patterns are systematically related to patients' personality pathology across therapeutic approaches, suggesting that clinicians, regardless of therapeutic orientation, can make diagnostic and therapeutic use of their own responses to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
344
7
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 323 publications
(415 citation statements)
references
References 50 publications
29
344
7
16
Order By: Relevance
“…The inverse relationship between these two variables is consistent with studies that relate the care of patients with specific personality disorders to characteristic countertransference feelings. [8][9][10][11]33 There were no significant associations in the sample stratified of patients seen by male therapists, probably due to the small sample size.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The inverse relationship between these two variables is consistent with studies that relate the care of patients with specific personality disorders to characteristic countertransference feelings. [8][9][10][11]33 There were no significant associations in the sample stratified of patients seen by male therapists, probably due to the small sample size.…”
Section: Discussionmentioning
confidence: 81%
“…The study by Betan et al showed significant correlation between specific countertransference patterns and personality disorders. 11 This suggests that countertransference responses may arise in a coherent and predictable manner, which strengthens its use for diagnostic unraveling and treatment of patients. The results of these studies support the possibility and the importance of identifying countertransference patterns triggered by patients with different psychiatric diagnoses, or by those sharing previous traumatic experiences, such as a history of sexual violence.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations